Scanning probe and optical tweezer investigations of biomolecular interactions - Rigby-Singleton, Shellie (2003)
A complex array of intermolecular forces controls the interactions between and within biological molecules. The desire to empirically explore these fundamental forces has led to the development of several biophysical techniques. Of these, the atomic force microscope (AFM) and the optical tweezers have been employed throughout this thesis to monitor the intermolecular forces involved in biomolecular interactions.